LAB of inclusive urbanism as a format to educate urban designers. - Mensing-de Jong, Angela; Racoń-Leja, Kinga; Zdrahálová, Jana (My University, 2020)
In this paper the didactic method known as the LAB is discussed, a short intensive programme in urban design developed in the years 2009-2019 by various Faculties of Architecture including the Technical University of Dresden, the Cracow University of Technology and the Czech Technical University in Prague. The main aim of this contribution is to introduce the LAB format in urban design education, stressing its innovative and inclusive aspects. The LAB includes the formulation of a spatial strategy based on the existing urban identity as well as socioeconomic and demographic conditions of a location; it brings a unique set of participants, collaborators and stakeholders to a site, hich is indispensable for an inclusive approach. The LAB provides a valuable format in addition to standard studio projects in urban design education. The preparatory phase involves an analysis of the case study, conducted remotely using geodata portals and with information provided by the local administration. To foster inclusiveness in this analytical phase, it is necessary to take account of pre-studies as well as particular on-site experience complemented by the knowledge and expertise of local government, NGOs and local residents. In the LAB, approx. 35 to 60 students consider complex historical, political, natural and cultural conditions, placing these in the context of the current spatial and social situation of the city. The added value is also the possibility of exchanging ideas, working methods and individual mapping skills by participants from various universities, countries and curricula (such as architecture, urban design, spatial planning and landscape architecture). Furthermore, the LAB serves as a useful platform for open discussion between local stakeholders and representatives of the administration. It supports objective debate, free of potentially conflicting political and financial considerations.
Keywords: Raumplanerausbildung; Planerausbildung; Städtebau; Stadtplanung; Unterrichtsmethode; Lehrmethode; Didaktik